FXR agonist GW4064 enhances anti-PD-L1 immunotherapy in colorectal cancer - Lu Lu; Yi-Xin Jiang; Xiao-Xia Liu; Jin-Mei Jin; Wen-Jie Gu; Xin Luan; Ying-Yun Guan; Li-Jun Zhang (OncoImmunology)
Colorectal cancer (CRC) is one of the top three malignant tumors in terms of morbidity, and the limited efficacy of existing therapies urges the discovery of potential treatment strategies. Immunotherapy gradually becomes a promising cancer treatment method in recent decades; however, less than 10% of CRC patients could really benefit from immunotherapy. It is pressing to explore the potential combination therapy to improve the immunotherapy efficacy in CRC patients. It is reported that Farnesoid X receptor (FXR) is deficiency in CRC and associated with immunity. Herein, we found that GW4064, a FXR agonist, could induce apoptosis, block cell cycle, and mediate immunogenic cell death (ICD) of CRC cells in vitro. Disappointingly, GW4064 could not suppress the growth of CRC tumors in vivo. Further studies revealed that GW4064 upregulated PD-L1 expression in CRC cells via activating FXR and MAPK signaling pathways. Gratifyingly, the combination of PD-L1 antibody with GW4064 exhibited excellent anti-tumor effects in CT26 xenograft models and increased CD8+ T cells infiltration, with 33% tumor bearing mice cured. This paper illustrates the potential mechanisms of GW4064 to upregulate PD-L1 expression in CRC cells and provides important data to support the combination therapy of PD-L1 immune checkpoint blockade with FXR agonist for CRC patients.